The contribution of new methods in cytology for increasing sensitivity in the diagnosis of extrahepatic bile duct lesions - Kurfurstova, Daniela; Slobodova, Zuzana; Zoundjiekpon, Vincent; Urban, Ondrej (Biomedical papers, 2023)
The aim of this review is to provide a comprehensive analysis of the existing literature pertaining to cytology of extrahepatic bile ducts. A search using the keywords ``biliary brush cytology'' was conducted in the PubMed database, with a focus on recent articles. The inclusion criteria primarily encompassed publications addressing problematic biliary stenosis. Emphasis was placed on identifying articles that explored innovative or less-utilized examination techniques aimed at enhancing the sensitivity of cytological examination. This review presents a comprehensive overview of the various types of materials used in sampling and the corresponding sampling methods. Additionally, it explores cytological and cytogenetic techniques, such as fluorescence in situ hybridization (FISH) and genetic methods (miRNA, NGS, cfDNA). These techniques possess the potential to improve the accuracy of diagnosing bile duct tumors, although their sensitivity varies. Furthermore, their utilization can facilitate early therapy, which plays a crucial role in patient prognosis. Each examination is always dependent on the quality and quantity of material delivered. A higher sensitivity of these examinations can be achieved by combining biliary cytology and other complementary methods.
Keywords: diagnosis of biliary strictures; cytology; fluorescence in situ hybridization; next generation sequencing; sensitivity